Дослідження матричних металевих коліматорів для просторово фракціонованої променевої терапії - Анохін, І.; Рамазанов, Д. (КОМП’ЮТЕРНО-ІНТЕГРОВАНІ ТЕХНОЛОГІЇ: ОСВІТА, НАУКА, ВИРОБНИЦТВО, 2023)
Traditional radiation therapy is hindered by limitations in dose delivery and the risk of over-irradiation, which can harm healthy tissues surrounding tumors. Spatially fractionated and intensity-modulated radiation therapies have emerged as promising techniques to mitigate these issues by reducing damage to healthy tissues. This study explores the potential of enhancing radiation therapy's therapeutic efficacy through spatial fractionation of X-ray beams, a technique that can significantly increase radiation efficiency by reducing the dose load on healthy tissues. This research hypothesizes that microscopic lesions within the paths of micro/mini-beams can be repaired by minimally irradiated cells adjacent to the irradiated tissue slices, based on observations with high-energy (MV) photons. Spatial fractionation is particularly valuable for X-ray and electron radiation therapy, which is more widespread and cost-effective than proton therapy. The study introduces a new type of cost-effective metal matrix collimators designed for beam fractionation. These collimators are constructed using lead plates for thickness variation implementation and employ a 5x5 hole matrix with 1 mm diameter and 3 mm pitch, covering an area of 14x14 mm². To visualize beam distribution, a Timepix detector, capable of providing real-time 2D beam profiles, was employed. Experiments were conducted using a medical LINAC with typical therapeutic energy ranging from 6 to 18 MeV. Results indicate that spatial fractionation can be achieved for X-ray radiation, with a PVDR of approximately 3 for a 3 cm lead collimator. However, issues with hole uniformity and blurring in the peak area prompted a shift to using copper collimators due to their superior manufacturing properties. This study presents a novel matrix collimator design made from various materials for shaping mini beams, aimed at improving the efficiency of spatial dose fractionation for different ionizing radiation types. Geant4 simulations have been instrumental in optimizing collimator features. The findings suggest that high levels of dose fractionization can be achieved for X-rays, electrons, and proton beams. These results warrant further biological studies to evaluate the effects of fractionation on normal and tumoral tissues, supporting the practical implementation of collimation in radiation therapy.